La ejecución en España de sentencias de nulidad, separación o divorcio dictadas por Tribunales extranjeros - Panizo y Romo de Arce, Alberto (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2006)
This study deals with the procedures envisaged in the Council Regulation (EC) 2201/03 of 27 November 2003 concerning the execution of marriage resolutions passed in countries of the European Community, including the analysis of the jurisdiction and terms of reference of these processes, that tend to become harmonised in these countries whenever the above-mentioned resolutions are to be executed in Community countries.